Characteristics and management of children with Clostridioides difficile infection at a tertiary pediatric hospital in China - Li,Xiaolu (2022)
ABSTRACT Background: Clostridiodes difficile infection (CDI) is one of the most common causes of antibiotic-associated diarrhea in children. Conventional antibiotics and emerging fecal micro-biota transplantation (FMT) are used to treat CDI. Methods: Children with CDI admitted to the Shanghai Children’s Hospital, from September 2014 to September 2020, were retrospectively included to this observational study. Pediatric patients were assigned as initial CDI and recurrent CDI (RCDI), and symptoms, comorbid-ities, imaging findings, laboratory tests, and treatments were systematically recorded and analyzed. Results: Of 109 pediatric patients with CDI, 58 were boys (53.2%), and the median age was 5 years (range, 2-9 years). The main clinical symptoms of CDI children were diarrhea (109/109, 100%), hematochezia (55/109, 50.46%), abdominal pain (40/109, 36.70%); fever, pseudomembrane, vomit, and bloating were observed in 39 (35.78%), 33 (30.28%), and 24 (22.02%) patients, respectively. For the primary therapy with conventional antibiotics, 68 patients received metronidazole, and 41 patients received vancomycin. RCDI occurred in 48.53% (33/68) of those initially treated with metronidazole compared with 46.33% (19/41) of those initially treated with vancomycin (p=0.825). The total resolution rate of FMT for RCDI children was significantly higher than with vancomycin treatment (28/29, 96.55% vs 11/23, 47.83%, p < 0.001). There were no serious adverse events (SAEs) reported after two months of FMT. Conclusions: The major manifestations of children with CDI were diarrhea, hematochezia, and abdominal pain. The cure rate of FMT for pediatric RCDI is superior to vancomycin treatment.